Stakeholder involvement in social marketing : challenges and approaches to engagement - Knox, Kathy; Kubacki, Krzysztof; Rundle-Thiele, Sharyn (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"This book is the first to provide evidence-based experiences to guide stakeholder management in social marketing interventions, as well providing contemporary discussions of social marketing research. The book aims to bring practitioners and academics together to address the calls made by scholars to address inherent challenges involved in identifying, involving and prioritising different stakeholders in social marketing interventions. Through sharing real-world experiences, the text aims to extend and synthesise current knowledge in the field and contribute to establishing stronger and long-lasting alliances with stakeholders involved in social marketing interventions for a sustainable behavioural change. This book features a diverse series of case studies from different countries (included but not limited to Australia, Finland, India, Slovenia, the United Kingdom) conducted in various behaviour change contexts (including alcohol consumption, nutrition intake, and breast feeding). Leading international social marketing scholars provide case studies on stakeholder involvement in an intervention or multiple interventions and elucidate relevant lessons to inform theoretical as well as practical implications for multi-stakeholder social marketing interventions. This volume will be of interest to researchers, advanced students, practitioners and policy makers in social marketing and health policy"--
OCLC-licensed vendor bibliographic record.
Keywords: Social marketing; Stakeholder management; Social change; BUSINESS & ECONOMICS / Marketing / Research; BUSINESS & ECONOMICS / Consumer Behavior